Simulation of square wave voltammetry at hemispherical electrodes: Electrochemically reversible, irreversible and quasi-reversible processes - Brookes, B; Macfie, G; Compton, R (2000)
A general approach is developed for the numerical simulation of square wave voltammetry (SWV) at hemispherical electrodes based on the backward implicit method. The latter is applied to the modeling of electrochemically reversible, irreversible and quasi-reversible redox couples. Data from the simulations are analyzed by comparing voltammograms for different hemispherical electrode radii with those for diffusion at uniformly accessible planar electrodes for a range of electrochemical rate constants so as to evaluate the qualitative effects of transport regime on the observed voltammetry. Experimental data are presented for the oxidation of 4-chloronitrobenzene in dimethylformamide solution at two disk electrodes of radii 250 and 12.5 μm. The peak current is recorded over a range of square wave frequencies and compared to results calculated from simulation of both planar and hemispherical electrodes. © 2000 American Chemical Society.